Analisa Tahanan Isolasi Pada Transformator Daya 150/30 Kv Gardu Induk Padang Luar PT PLN (PERSERO) Bukittinggi - Arinsya Prima, Gilang Arinsya (Indonesian Journal of Engineering and Technology (INAJET), 2023)
This research aims to test the feasibility of a 2 30 MVA power transformer at the Padang Luar Main Substation which is more than 10 years old. The suitability of this transformer refers to the results of measurements using winding insulation resistance test parameters, Polarization Index (IP), winding delta tangent, and breakdown voltage (BDV) of transformer oil using international test standards (IEEE, IEC and CIGRE). The measurement results obtained are then compared with the calculations, then by referring to the standards it will be known whether the transformer is still suitable for operation or not. The results of the insulation resistance test on the 2 30 MVA GI Padang Luar power transformer showed that the insulation resistance value was in the range of 8.91 – 29.7 GΩ and the polarization index was in the range of 1.77 – 2.55. Tangent delta testing produces results between 0.1706 – 0.8708%. In the breakdown voltage test, a value of 59.3 kV/2.5 mm was obtained for the top oil and 57.6 kV/2.5 mm for the bottom oil. The test results obtained are the same as calculations using the calculation formula. Based on the test results with the parameters above then referring to IEEE, IEC and CIGRE standards, the 2 30 MVA GI Padang Luar power transformer is still suitable for operation even though it is more than 10 years old. Keywords: transformer feasibility, power transformer testing, international standards, 2 30 MVA power transformer, GI Padang Luar.